Mast cell leukemia: clinical and molecular features and survival outcomes of patients in the ECNM Registry - Kennedy, Vanessa; Perkins, Cecelia; Reiter, Andreas; Jawhar, Mohamad; Lübke, Johannes; Kluin-Nelemans, Hanneke C.; Shomali, William; Langford, Cheryl; Abuel, Justin; Hermine, Olivier; Niedoszytko, Marek; Gorska, Aleksandra; et al. (Blood advances, 2023)
Mast cell leukemia (MCL) is a rare subtype of systemic mastocytosis defined by ≥20% mast cells (MC) on a bone marrow aspirate. We evaluated 92 patients with MCL from the European Competence Network on Mastocytosis registry. Thirty-one (34%) patients had a diagnosis of MCL with an associated hematologic neoplasm (MCL-AHN). Chronic MCL (lack of C-findings) comprised 14% of patients, and only 4.5% had “leukemic MCL” (≥10% circulating MCs). KIT D816V was found in 62/85 (73%) evaluable patients; 9 (11%) individuals exhibited alternative KIT mutations, and no KIT variants were detected in 14 (17%) subjects. Ten evaluable patients (17%) had an abnormal karyotype and the poor-risk SRSF2, ASXL1, and RUNX1 (S/A/R) mutations were identified in 16/36 (44%) patients who underwent next-generation sequencing. Midostaurin was the most common therapy administered to 65% of patients and 45% as first-line therapy. The median overall survival (OS) was 1.6 years. In multivariate analysis (S/A/R mutations excluded owing to low event rates), a diagnosis of MCL-AHN (hazard ratio [HR], 4.7; 95% confidence interval [CI], 1.7-13.0; P = .001) and abnormal karyotype (HR, 5.6; 95% CI, 1.4-13.3; P = .02) were associated with inferior OS; KIT D816V positivity (HR, 0.33; 95% CI, 0.11-0.98; P = .04) and midostaurin treatment (HR, 0.32; 95% CI, 0.08-0.72; P = .008) were associated with superior OS. These data provide the most comprehensive snapshot of the clinicopathologic, molecular, and treatment landscape of MCL to date, and should help further inform subtyping and prognostication of MCL.